Ética en el modelo de provisión de cuidados. ¿Te elijo o me eliges? (Paraninfo Digital, 2024)
.
Keywords: s:5:"Ética"; s:8:"Cuidados"; s:23:"Gestión público privada"; s:11:"Dependencia"; s:19:"Modelos de atención"; s:18:"Servicios sociales"